Systematic review: ibuprofen-induced liver injury. - Zoubek, Miguel E.; Lucena-González, María Isabel; Andrade-Bellido, Raúl Jesús; Stephens, Camilla (Wiley-Blackwell, 2020)
Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are a leading cause of drug-induced liver injury (DILI) across the world. Ibuprofen is one of the most commonly used and safest NSAIDs, nevertheless reports on ibuprofen-induced hepatotoxicity are available. Aim: To analyse previously published information on ibuprofen-induced liver injury for a better characterisation of its phenotypic expression. Method: A systematic search was performed and information on ibuprofen-induced liver injury included in case series and case reports, in terms of demographic, clinical, biochemical and outcome data, was analysed. Results: Twenty-two idiosyncratic ibuprofen hepatotoxicity cases were identified in the literature, suggesting a very low prevalence of this type of DILI. These patients had a mean age of 31 years and 55% were females. Mean cumulative dose of ibuprofen and time to onset were 30 g and 12 days, respectively. Hepatocellular injury was the most frequently involved liver injury pattern. Six cases developed vanishing bile duct syndrome. Full recovery occurred in 11 patients after a mean time of 14 weeks, whereas five cases evolved to acute liver failure leading to death/liver transplantation. Conclusions: When assessing potential hepatotoxicity cases, physicians should keep in mind that ibuprofen has been associated with hepatotoxicity in the literature. Ibuprofenassociated DILI presents commonly as hepatocellular damage after a short latency period. Published reports on ibuprofen hepatotoxicity leading to liver failure resulting in liver transplantation or death are available. However, due to the apparent low absolute risk of ibuprofen-induced liver complications, ibuprofen can be regarded as an efficacious and safe NSAID.
https://openpolicyfinder.jisc.ac.uk/id/publication/81
Keywords: Hepatotoxicidad; Hígado - Heridas y lesiones; Ibuprofeno - Efectos secundarios; Revisiones sistemáticas (Medicina); Hepatotoxicity; Adverse reaction